FEUDAL ALLOCATIONS IN BRAZIL, SOCIAL SEGREGATION AND THE REMOVAL OF CITIZENSHIP (Reflection and Critique Law Magazine, 2022)
ABSTRACT The purpose of this article is to analyze the new closed system of subdivisions built in Brazil with the purpose of bringing to its inhabitants a real housing fortress with a little bit of everything related to the city, from the possibility of shopping, leisure, security, practice sports, among others, establishing new traffic patterns, rules of conduct and behavior. These ventures that bring the citizen to a superficial reality that removes the citizen from the usual daily concerns of his city can we call new fiefdoms? This article deals exactly with that, analyzing real estate developments with a retrograde look in the search for an epistemic definition.Keywords: Condominium. Allotment. Feud. Citizenship. Citizen. Segregation.